The Influence Of Price And Promotion On Consumer Buying Interest At Indomaret Bandar Lampung - Arafat, Ahmad Aldi; Warganegara, Tri Lestira Putri (Indonesian Journal Economic Review (IJER), 2025)
This study aims to examine the effect of price and promotion on consumer buying interest at Indomaret Bandar Lampung. Price is a critical factor in determining whether consumers will accept or reject a product. The right pricing strategy can increase consumer appeal and influence purchasing decisions. Meanwhile, promotion serves as a tool to introduce products to the public and persuade consumers to choose a particular product. This research employs a quantitative approach with a sample size of 100 consumers. Data analysis is conducted using multiple linear regression to assess the impact of price and promotion on buying interest. The findings show that: 1) Price has a positive and significant impact on consumer buying interest at Indomaret Bandar Lampung, 2) Promotion also has a positive and significant effect on buying interest, 3) Together, price and promotion have a positive and significant influence on consumer buying interest. These results are expected to assist Indomaret managers in formulating more effective pricing and promotional strategies to boost consumer buying interest.